Answer :

The roots of a quadratic equation will satisfy the equation - start with option 1


A. x2 - 3x + 10 = 0


For x = 5


52 - (3.5) + 10


25 - 15 + 10 = 20 ≠ 0


Hence this is not the equation


B. x2 - 3x - 10 = 0


For x = 5


52 - (3.5) - 10 = 25 - 15 - 10


= 25 - 25 = 0


For x = - 2


= ( - 2)2 - (3. - 2) - 10


= 4 + 6 - 10 = 10 - 10 = 0


This equation is satisfied for both the roots.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses